2020
DOI: 10.1515/jib-2019-0073
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optimization-Modelling Methods for Metabolites Production inEscherichia coli

Abstract: The metabolic network is the reconstruction of the metabolic pathway of an organism that is used to represent the interaction between enzymes and metabolites in genome level. Meanwhile, metabolic engineering is a process that modifies the metabolic network of a cell to increase the production of metabolites. However, the metabolic networks are too complex that cause problem in identifying near-optimal knockout genes/reactions for maximizing the metabolite’s production. Therefore, through constraint-based model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Experiments showed that ethanol production reached a maximum of 17.2270 mmolh −1 gDW −1 with three genes knocked out, while growth rate reached a maximum of 0.2338 h −1 with five genes knocked out. One year later, Lee et al compared the performance of PSOMOMA with CSMOMA and ABCMOMA for the succinate yield maximization method in E. coli [74]. The results of PSOMOMA were validated with the results of wet-lab experiments.…”
Section: Particle Swarm Optimization Algorithm (Pso)mentioning
confidence: 99%
“…Experiments showed that ethanol production reached a maximum of 17.2270 mmolh −1 gDW −1 with three genes knocked out, while growth rate reached a maximum of 0.2338 h −1 with five genes knocked out. One year later, Lee et al compared the performance of PSOMOMA with CSMOMA and ABCMOMA for the succinate yield maximization method in E. coli [74]. The results of PSOMOMA were validated with the results of wet-lab experiments.…”
Section: Particle Swarm Optimization Algorithm (Pso)mentioning
confidence: 99%
“…Comprehensive carbon metabolism model (375 reactions) to analyze the metabolism and predict knockout strategies for maximum SA production with maintaining the cell growth 2018 [95] A. succinogenes Genome-scale metabolic model to evaluate the metabolic capability of the strain to produce SA under various conditions 2018 [30] Zymomonas mobilis Genome-scale metabolic model to characterize SA-producing capability and comparatively identify gene deletions for enhanced SA production 2018 [96] E. coli Optimization modeling to identify near-optimal knockout genes for the maximum production of SA 2020 [97] Aspergillus niger…”
Section: E Coli and A Succinogenesmentioning
confidence: 99%
“…Unlike data-driven modeling, optimization- and enumeration-based strategies can be used to investigate and characterize a biochemical network from first principles and at the near-steady state ( Segre et al, 2002 ; Shlomi et al, 2005 ; Wagner and Urbanczik, 2005 ; Urbanczik, 2007 ; Orth et al, 2010 ; Muller and Regensburger, 2016 ; Klamt et al, 2017 ; Klamt et al, 2018 ; Lee et al, 2020 ). Algorithms which assess the flux of a reactant (flux balance analysis, flux variability analysis, regulatory on–off minimization, and minimization of metabolic adjustment) will maximize or minimize the biomass of a metabolite of interest and can be used to investigate the effects of deletions and other perturbations on the flux of metabolites through a large network ( Segre et al, 2002 ; Shlomi et al, 2005 ; Orth et al, 2010 ; Klamt et al, 2018 ; Lee et al, 2020 ). The numerical enumeration of elementary flux modes and vectors, along with extreme pathway analysis, can be used to derive meaningful information about “metabolic” hubs and smaller subsets of cooperating reactions from biochemical networks ( Wagner and Urbanczik, 2005 ; Urbanczik, 2007 ; Muller and Regensburger, 2016 ; Klamt et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%